The Level of Writing Apprehension on Students’ EFL Writing Class: A Case Study - Nurdianingsih, Fitri Nurdianingsih,; Rohmah, Ima Isnaini Taufiqur; Wahyuni, Sri; Izzatisselim, Zilvia Nur (FKIP Universitas Lampung, 2025)
The Level of Writing Apprehension on Students; EFL Writing Class: A Case Study. Objective: This study aims to investigate the level of writing apprehension among students enrolled in an English as a Foreign Language (EFL) writing class, specifically within the Expository and Argumentative Writing Course; Methods: The qualitative case study design involved 35 undergraduate students from the English Education Department IKIP PGRI Bojonegoro. Data was collected using a modified version of Daly and Miller (1975) Writing Apprehension Questionnaire (WAQ). Open-ended responses were analzed using descriptive statistics and thematic coding. Findings: The results revealed varying levels of writing apprehension. Approximately 40% of the students experienced writing apprehension, which impacted their capacity to use language, structure their ideas, and use grammar. On the other hand, 63% of participants said they felt less nervous, which they attributed to their prior success and growing confidence in their writing. Qualitative research revealed several pertinent factors, such as poor language skills, past academic setbacks, and fear of a negative evaluation. It was discovered that methods like peer review, process writing, and self-control were effective in reducing apprehension. Conclusion: Writing apprehension is a prevalent issue in EFL settings that necessitates targeted instructional interventions. This study highlights the importance of using supportive writing pedagogies to help students become more confident and proficient writers. Further research into the long-term effectiveness of apprehension-reduction strategies is necessary, especially in digital or hybrid writing contexts, as the findings highlight the emotional challenges faced by EFL students. Keywords: EFL writing, writing apprehension, writing achievement.